Divine soul mind body healing and transmission system : - Sha, Zhi Gang (Atria Books, 2009)
This book gives you the soul secrets, wisdom, knowledge, and practices of this divine soul healing system. In this remarkable and uplifting guide to physical health, emotional wellness, and spiritual fulfillment, Dr. Sha reveals practical techniques to heal you, your loved ones, pets, relationships, finances, organizations, Mother Earth, and humanity.